Allan Nevins Is Not My Grandfather: The Roots of Radical Oral History Practice in the United States. (1st September 2016) - Kerr, Daniel R.
Abstract: Oral historians in the United States have adopted a problematic history of our field that erases the contributions of our radical forbearers. By fixating on recording technologies, archives, and academia, we ignore those who have shaped the theories and methodologies we draw upon when we facilitate dialogues grounded in personal experiences and interpretive reflections on the past. This article identifies the direct contributions that popular educators such as Myles Horton, Septima Clark, Ella Baker, and Paolo Freire played in shaping the field of oral history in the United States. Furthermore, it highlights the role that Staughton and Alice Lynd, Helen Lewis, the Massachusetts History Workshop, and the Brass Workers History Project played in translating these popular education practices into current oral history theories and methods.